West Nile Virus Infection in Pregnancy - Robert D. Stewart; Stefanie N. Bryant; Jeanne S. Sheffield (Case Reports in Infectious Diseases)
A recent outbreak of West Nile virus has allowed for observations as to the clinical course of this emerging pathogen during pregnancy. We present three cases of West Nile virus infection during pregnancy. Case 1 presented at term with focal subjective weakness and fever. With supportive care, her symptoms were resolved within 7 days, and she subsequently delivered an unaffected term infant. Case 2 presented in the first trimester with fever and headache. Her symptoms were resolved in 8 days with supportive care. Case 3 was diagnosed during the first trimester during workup of nonspecific respiratory symptoms, with resolution of all symptoms in 24 days. Obstetricians need to be aware of the varied clinical presentation of West Nile virus during pregnancy.